Pengaruh Psychological First Aid (PFA) Dan Psikoedukasi Terhadap Regulasi Emosi Remaja Korban Bullying - Yeni Suryaningsih; Ely Rahmatika Nugrahani (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Bullying among adolescents can lead to emotional regulation disturbances that negatively impact mental health and social adjustment. Interventions aimed at improving emotional regulation in adolescent victims of bullying include Psychological First Aid (PFA) and psychoeducation. This study aimed to analyze the effects of PFA, psychoeducation, and their combination on the emotional regulation of adolescent bullying victims. A quasi-experimental design with a pretest–posttest control group approach was employed. The sample consisted of 21 respondents divided into three groups (PFA, psychoeducation, and combination), with 7 participants in each group. The interventions were conducted over eight sessions, each lasting 60 minutes. Data were analyzed using the Wilcoxon test and Kruskal–Wallis test followed by Post Hoc Mann–Whitney (α < 0.05). The results showed significant improvements in emotional regulation in the PFA group (p = 0.016), psychoeducation group (p = 0.017), and combination group (p = 0.018). The Kruskal–Wallis test indicated significant differences among the three groups (p = 0.001). Post Hoc analysis revealed that the combination of PFA and psychoeducation was more effective than either intervention alone (p = 0.002). In conclusion, all three interventions significantly improved emotional regulation, with the combined intervention being the most effective.